2014
DOI: 10.1002/pssb.201350347
|View full text |Cite
|
Sign up to set email alerts
|

Application of the paracrystal model to GISAXS analysis of the 3D self-assembled nanoparticle crystals

Abstract: An original diffraction model for the evaluation of the grazing‐incidence small‐angle X‐ray scattering (GISAXS) of the three‐dimensional (3D) supported self‐assembled nanoparticle crystals is presented. The model utilizes the formalism of traditional crystallography that is applied to nanoparticles as scattering entities. The infinite paracrystal concept was adopted in order to include cumulative disorder that is typical for the self‐assembled nanoparticle structures. Azimuthal averaging around a chosen crysta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 52 publications
(104 reference statements)
0
2
0
Order By: Relevance
“…S3.2. For more detailed developement of these models, the reader is referred to the work of Hosemann [4,5], Guinier [6], and others [7,8,9,10].…”
Section: S3 Models Of Propagating and Non-propagating Lattice Disordermentioning
confidence: 99%
See 1 more Smart Citation
“…S3.2. For more detailed developement of these models, the reader is referred to the work of Hosemann [4,5], Guinier [6], and others [7,8,9,10].…”
Section: S3 Models Of Propagating and Non-propagating Lattice Disordermentioning
confidence: 99%
“…Though the polydispersity of QD building blocks used here was only ∼6%, which represents approximately a single lattice plane spacing, any polydispersity should in principle result in paracrystallinity (see Supporting Information S3), and recent GISAXS studies have concluded that unconnected colloidal crystal thin films are paracrystalline. 25 However, the superiority of the real paracrystal model has not yet been demonstrated in either unconnected or connected colloidal crystals and is essential to understanding the relationship between short and long-range SL order. These structural distinctions may have dramatic implications for electronic transport in CBCs.…”
Section: Nano Lettersmentioning
confidence: 99%